Fellowship training in microvascular surgery and post-fellowship practice patterns: a cross sectional survey of microvascular surgeons from facial plastic and reconstructive surgery programs - Douglas M. Bennion; Peter T. Dziegielewski; Brian J. Boyce; Yadro Ducic; Raja Sawhney (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background There is a lack of published literature on the training in microvascular reconstructive techniques in facial plastic and reconstructive surgery (FPRS) fellowships or of the extent these techniques are continued in practice. This cross-sectional web-based survey study was conducted to describe the volume, variety, and intended extent of practice of free tissue transfers during fellowship and the post-fellowship pattern of microsurgical practice among FPRS surgeons in various private and academic practice settings across the United States. Methods This survey was sent to recent graduates (n = 94) of a subset of U.S. Facial Plastic and Reconstructive Surgery fellowship programs that provide significant training in microvascular surgery. Results Among survey respondents (n = 21, 22% response rate), two-thirds completed 20–100 microvascular cases during fellowship using mainly radial forearm, fibula, anterior lateral thigh, latissimus and rectus free tissue transfers. In post-fellowship practice, those who continue practicing microvascular reconstruction (86%) complete an average of 33 cases annually. The choice of donor tissues for reconstruction mirrored their training. They are assisted primarily by residents (73%) and/or fellows (43%), while some worked with a micro-trained partner, surgical assistant, or performed solo procedures. Interestingly, among those who began in private practice (29%), only half remained with that practice, while those who joined academic practices (71%) largely remained at their initial post-fellowship location (87%). Conclusions These results provide the first formal description of the training and practice patterns of FPRS-trained microvascular surgeons. They describe a diverse fellowship training experience that often results in robust microvascular practice. The maintenance of substantial microsurgical caseloads after fellowship runs counter to the perception of high levels of burnout from free tissue transfers among microvascular surgeons. Trial Registration This study was approved as exempt by the University of Florida Institutional Review Board (#201601526).